Reining in BTK: Interdomain Interactions and Their Importance in the Regulatory Control of BTK - Kueffer, Lauren E.; Joseph, Raji E.; Andreotti, Amy H. (Frontiers in Cell and Developmental Biology, 2021)
Since Dr. Ogden Bruton’s 1952 paper describing the first human primary immunodeficiency disease, the peripheral membrane binding signaling protein, aptly named Bruton’s tyrosine kinase (BTK), has been the target of intense study. Dr. Bruton’s description of agammaglobulinemia set the stage for ultimately understanding key signaling steps emanating from the B cell receptor. BTK is a multidomain tyrosine kinase and in the decades since Dr. Bruton’s discovery it has become clear that genetic defects in the regulatory domains or the catalytic domain can lead to immunodeficiency. This finding underscores the intricate regulatory mechanisms within the BTK protein that maintain appropriate levels of signaling both in the resting B cell and during an immune challenge. The survival reliance of B cell malignancies on B cell receptor signaling has allowed small molecules that target BTK to become essential tools in treating patients with hematological malignancies. The first-in-class Ibrutinib and more selective second-generation inhibitors all target the active site of the multidomain BTK protein. Therapeutic interventions targeting BTK have been successful but are plagued by resistance mutations that render drug treatment ineffective for some patients. This review will examine the molecular mechanisms that drive drug resistance, the long-range conformational effects of active site inhibitors on the BTK regulatory apparatus, and emerging opportunities to allosterically target the BTK kinase to improve therapeutic interventions using combination therapies.